2020
DOI: 10.1097/txd.0000000000001026
|View full text |Cite
|
Sign up to set email alerts
|

Educational Animations to Inform Transplant Candidates About Deceased Donor Kidney Options: An Efficacy Randomized Trial

Abstract: Background. Transplant candidates struggle making decisions about accepting kidneys with variable kidney donor profile index (KDPI) and increased risk donor (IRD) status. Methods. This single site, pilot randomized controlled trial evaluated the efficacy of 2 animations to improve KDPI/IRD knowledge, decisional self-efficacy, and willingness. Kidney candidates were randomly assigned to animation viewing plus standard nurse discussion (intervention) or standard nurse dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(56 citation statements)
references
References 33 publications
0
56
0
Order By: Relevance
“…Both videos could be paused and replayed an unlimited number of times. After video viewing was complete, participants answered 1 question about whether they watched the videos and the device used, followed by survey questions identical to the pre-tests, with the sociodemographic questions replaced by animation acceptability questions (11 items, 5-point Likert scale), which was developed by the researchers (α=0.92) [ 38 ]. All survey questions were required and posed sequentially without the option of going backward.…”
Section: Methodsmentioning
confidence: 99%
“…Both videos could be paused and replayed an unlimited number of times. After video viewing was complete, participants answered 1 question about whether they watched the videos and the device used, followed by survey questions identical to the pre-tests, with the sociodemographic questions replaced by animation acceptability questions (11 items, 5-point Likert scale), which was developed by the researchers (α=0.92) [ 38 ]. All survey questions were required and posed sequentially without the option of going backward.…”
Section: Methodsmentioning
confidence: 99%
“…Of these, 1245 studies did not meet inclusion criteria. Full-text reviews (or review of abstracts retained in order to contact the authors to determine if a full-text manuscript had been published), were conducted on the resulting 101 studies, yielding 12 studies [41][42][43][44][45][46][47][48][49][50][51][52] for the systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…Each set of videos was always viewed in the same order. Immediately after viewing the designated video set (T1), participants completed the post‐tests containing the same questions as the pretest, followed by a 12‐item Video Acceptability survey (α = .92; 5‐point Likert) that was developed by the researchers 23 . Research staff then showed participants how to navigate the web platform.…”
Section: Study Protocolmentioning
confidence: 99%
“…Immediately after viewing the designated video set (T1), participants completed the post-tests containing the same questions as the pretest, followed by a 12-item Video Acceptability survey (α = .92; 5-point Likert) that was developed by the researchers. 23 Research staff then showed participants how to navigate the web platform. The platform offers users the ability to select which videos they would prefer to watch rather than a set sequential order (Figure 1).…”
Section: Study Protocolmentioning
confidence: 99%